Thorium Based Indian Nuclear Program - Hussain, Waqar; AHMAD, KHURRAM MAQSOOD; Azam, Adeela; Rehman, Sidra (The Nucleus, 2023)
India has the largest thorium reserves in the world. Normally, it is deposited in the rocks and can be extracted through specific processing, however, in India, it is available in pure and refined form. India has included utilization of Thorium as a major goal in its nuclear energy program because it has the large amount of thorium as compared to meager uranium reserves. Indian ambitious three stage nuclear program is aimed to fulfill its objective to achieve energy security whereas nearly 300 million of the population in India is estimated to be out of the national electricity grid. India is expanding its nuclear energy production to achieve the target of 63 GW into the total power share by 2032 and plans to further increase this share to 25% by 2050. However, the technology to use thorium as a fuel is quite complicated and no country has yet achieved this capability owing to the involvement of reprocessed nuclear fuel, which is quite hard to handle. While India is struggling to achieve a breakthrough in the development of technology to use thorium as blanket fuel for use in advanced reactor. The overall implications of such developments would result in the exponential increase in Indian fissile materials consequently jeopardizing the deterrence stability in South Asia. Once India is able to tap the weapon grade U-233 from thorium, then its fissile material stocks would increase exponentially resulting in exacerbating the Pakistani security dilemma vis-à-vis India.